Впровадження системи ХАССП у виробництва харчової продукції : методичні вказівки до практичних занять для здобувачів вищої освіти другого (магістерського) рівня денної форми здобуття освіти за спеціальністю 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» [Електронний ресурс] - Цихановська, Ірина Василівна; Лазарєва, Тетяна Анатоліївна; Гладкоскок, Анастасія Андріївна; Tsykhanovska, Iryna Vasylivna; Lazareva, Tatyana Anatoliivna; Gladkoskok, Anastasia Andriivna (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Методичні вказівки для здобувачів вищої освіти другого (магістерського) рівня денної форми здобуття освіти спеціальності 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» містять рекомендації щодо виконання практичних занять. Рекомендації складено відповідно до програми дисципліни «Біологічно активні сполуки в харчових продуктах», яка викладається магістрам 1 курсу спеціальності 015 «Професійна освіта (Аграрне виробництво, переробка сільськогосподарської продукції та харчові технології)» ХНУ імені В.Н. Каразіна. Методичні вказівки допоможуть здобувачам вищої освіти засвоїти теоретичний курс і набути практичних навичок.

Methodological guidelines for higher education applicants of the second (master's) level of full-time education in the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» contain recommendations for the implementation of practical classes. The recommendations are compiled in accordance with the program of the discipline «Implementation of the HACCP system in the production of food products», which is taught to 1st year masters of the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» of the V.N. Karazin KhNU. Methodological guidelines will help higher education applicants master the theoretical course and acquire practical skills.
Implementation of the HACCP system in food production : methodological instructions for practical classes for students of the second (master's) level of full-time higher education in the specialty 015 «Professional education (Agricultural production, processing of agricultural products and food technologies)» [Electronic resource]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: SOCIAL SCIENCES::Business and economics; TECHNOLOGY::Chemical engineering::Food technology; TECHNOLOGY::Industrial engineering and economy::Manufacturing engineering and work sciences; TECHNOLOGY::Industrial engineering and economy::Manufacturing engineering and work sciences; TECHNOLOGY::Industrial engineering and economy::Industrial organisation, administration and economics; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science::Food science; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Agricultural engineering; INTERDISCIPLINARY RESEARCH AREAS::Domestic science and nutrition; система управління якості ХАССП; принципи; впровадження; харчова галузь; HACCP quality management system; principles; implementation; food industry